Genetic Variability and Character Association Analysis in Wheat (Triticum aestivum L.) in Saline Water Condition - Mundiyara, Rajdeep; Yadav, Giradhari Lal; Bajiya, Rohitash; Singh, Ishwar; Bhardwaj, Rahul; Meena, Vikram; Kumari, Varsha (International Journal of Bio-resource and Stress Management, 2024)
The study was conducted to evaluate eight germplasms/varieties of wheat during the rabi season (November-April, 2022–23) using a randomized block design with three replications at the research farm of Agricultural Research Sub-Station (ARSS), Nagaur (Rajasthan), India to estimate the variability parameters and characters association for nine characters. The results were revealed that mean sum of squares due to genotypes showed significant differences for all the nine characters under study, suggested that the genotypes were genetically divergent. The phenotypic coefficient of variation values was higher than genotypic coefficient of variation values for all the nine traits which reflect the influence of environment on the expression of traits. Spike length and number of spikelets were showed higher PCV and medium GCV. High heritability estimates were recorded for all the nine characters. High genetic advance as percentage of mean along with high heritability was observed for number of spikelets, spike length, number of effective tillers plant-1, seed yield and number of grains spike-1. This indicated the existence of lesser environmental influence and prevalence of additive gene action in their expression and these traits possessed high selective value. These characters could be further improved through individual plant selection. Grain yield had highly significant and positive genotypic and phenotypic correlations with plant height, number of effective tillers plant-1, spike length, number of spikelets and number of grains spike-1. These characters can be considered as criteria for selection for higher grain yield as these were mutually and directly associated with grain yield.